Analysis of Routine Blood Profile as Data Supporting for Nursing Assessment in Breast Cancer Patients Undergoing Chemotherapy Treatment at the RSU. Dr. Wahidin Sudirohusodo - Yuliana Syam; Prihantono Prihantono; Elly Lilianty Sjattar; Arnis Puspitha (Journal of Health Science and Prevention, 2019)
Chemotherapy is one of the modality therapies given to breast cancer patients to inhibit cancer cell metastases. The side effects of chemotherapy can suppress the hematopoietic system in the bone marrow and progressively affect the patient's prognosis. The aim of study was to analyze routine blood profiles as supporting data in developing nursing care for breast cancer patients undergoing chemotherapy at the RSU. Dr. Wahidin Sudirohusodo Makassar, Indonesia, from June to September 2018. This research was a descriptive research with descriptive survey method. This research was conducted at the RSU Surgical Polyclinic. Dr. Wahidin Sudirohusodo. The sampling technique used was Non-Probability Sampling a purposive sampling method. The participants of this study were patients with breast cancer who undergo chemotherapy treatment with a number of samples that meet the inclusion criteria as many as 32 people. of the 17 routine blood components which were assessed as one of the investigations in 32 patients were found to be 4 abnormal components, red blood cells mean ± SD (3.99 10^6/ uL ± 0.51), hemoglobin mean ± SD (11.18 gr/l ± 1.09), hematocrit mean ± SD (34.96% ± 3.96), and mean ± SD monocyte (15,043 10^3/uL ± 8.95). due to metastasis and side effects of chemotherapy treatment decrease red blood cells, hemoglobin, hematocrit, and increase in specific immune response through increase of monocytes indicator that performing phagocytosis.